Systemic Symbiosis Management (SSM) : an Approach other than Joint Forest Management - the Case of Jaldapara Wildlife Sanctuary, 1985 - Rishi, Vinod (Indian Forester, 2011)
More than a century before the launching of India’s nation-wide programs of Joint Forest Management and Eco-development in 1990, Sir Dietrich Brandis, the founder of the Forest Department in India, had indicated the importance of human society in successful management of forests. India’s experience in limited success in saving its tigers, forests, and emerging public attitude of violence against forest staff and wild animals is an alarming indicator of problems which the current approaches in forest and wildlife conservation could not address. The present case study relates to the application of an approach in which a similar situation had been handled successfully for both forest and wildlife conservation in Jaldapara wildlife sanctuary in 1985.